New insights into intestinal macrophages in necrotizing enterocolitis: the multi-functional role and promising therapeutic application - Wei, Jiaqi; Meng, Zhaoli; Li, Zhenyu; Dang, Dan; Wu, Hui (Frontiers in Immunology, 2023)
Necrotizing enterocolitis (NEC) is an inflammatory intestinal disease that profoundly affects preterm infants. Currently, the pathogenesis of NEC remains controversial, resulting in limited treatment strategies. The preterm infants are thought to be susceptible to gut inflammatory disorders because of their immature immune system. In early life, intestinal macrophages (IMφs), crucial components of innate immunity, demonstrate functional plasticity and diversity in intestinal development, resistance to pathogens, maintenance of the intestinal barrier, and regulation of gut microbiota. When the stimulations of environmental, dietary, and bacterial factors interrupt the homeostatic processes of IMφs, they will lead to intestinal disease, such as NEC. This review focuses on the IMφs related pathogenesis in NEC, discusses the multi-functional roles and relevant molecular mechanisms of IMφs in preterm infants, and explores promising therapeutic application for NEC.